Electrochemical characterization of the paste carbon modified electrode with KSr2Ni0.75Nb4.25O15-delta solid in catalytic oxidation of the dipyrone - Dadamos, Tony R. L. [UNESP]; Freitas, Bruno H. [UNESP]; Genova, Diego H. M. [UNESP]; Espirito-Santo, Rafael D. [UNESP]; Perez Gonzalez, Eduardo R. [UNESP]; Lanfredi, Silvania [UNESP]; Teixeira, Marcos F. S. [UNESP] (Elsevier B.V. Sa, 2012)
The electrochemical behavior of a carbon paste electrode modified (CPEM) with nickel-doped potassium strontium niobate (KSr2Ni0.75Nb4.25O15-delta) of tetragonal tungsten bronze (TTB)-type structure was investigated as a new sensor for dipyrone. The optimum conditions were found in an electrode composition (in mass) of 20% KSr2Ni0.75Nb4.25O15-delta, 65% graphite and 15% mineral oil in 0.5 mol L-1 KCl solution at pH 6.0. The electrode exhibits reversible electrochemical behavior in a wide potential range (0.1-0.7 V vs. SCE), high conductivity, and stability/durability electrode in 0.50 mol L-1 KCl solution. The estimated surface concentration was found to equal 1.08 x 10(-9) mol cm(-2). The oxidation of dipyrone was performed at carbon paste electrode unmodified at +0.54 V vs. SCE and carbon paste electrode modified with KSr2Ni0.75Nb4.25O15-delta at +0.45 V vs. SCE. This result shows that the nickel-doped potassium strontium niobate on electrode surface promotes the oxidation of dipyrone. The reaction can be brought about electrochemically, where the niobium(IV) is first oxidation to a niobium(IV) oxide at the electrode surface. The niobium(IV) then undergoes a catalytic reduction by the dipyrone in solution back to the niobium(III), which can then be electrochemically re-oxidized to produce an enhancement of the anodic current. The identification of the oxidation product of dipyrone was made by mass spectrometry for elucidation of response mechanism of the sensor. Anodic peak current (I-pa) vs. dipyrone concentration for amperometric method at the modified electrode was linear in the 3.5 x 10(-5) and 3.1 x 10(-4) mol L-1 concentration range and the detection limit was 5.1 x 10(-6) mol L-1 dipyrone. At higher concentrations (>3.1 x 10(-4) mol L-1), deviation from linearity occurs. Under this condition, an electrocatalytic reaction takes place and proceeds through a mechanism similar to the Michaelis-Menten model. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Tetragonal tungsten bronze (TTB)-type structure; Dipyrone oxidation; Amperometric measurements; X-ray diffraction; MS spectrum